2015
DOI: 10.1016/j.yfrne.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The omniscient placenta: Metabolic and epigenetic regulation of fetal programming

Abstract: Fetal development could be considered a sensitive period wherein exogenous insults and changes to the maternal milieu can have long-term impacts on developmental programming. The placenta provides the fetus with protection and necessary nutrients for growth, and responds to maternal cues and changes in nutrient signaling through multiple epigenetic mechanisms. The X-linked enzyme O-linked-N-acetylglucosamine transferase (OGT) acts as a nutrient sensor that modifies numerous proteins to alter various cellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
143
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(153 citation statements)
references
References 151 publications
0
143
0
5
Order By: Relevance
“…Sex differences have been documented in human and animal models at multiple steps within fetal programming pathways including maternal-fetal glucocorticoid regulation, placental structure and function, and in offspring neurodevelopmental outcomes following prenatal perturbations (Bale, 2011; J. A. DiPietro et al, 2011; Nugent & Bale, 2015; Rosenfeld, 2015; Sandman, Glynn, & Davis, 2013). Sandman and colleagues have proposed an early-life viability-later-life vulnerabilty trade-off for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences have been documented in human and animal models at multiple steps within fetal programming pathways including maternal-fetal glucocorticoid regulation, placental structure and function, and in offspring neurodevelopmental outcomes following prenatal perturbations (Bale, 2011; J. A. DiPietro et al, 2011; Nugent & Bale, 2015; Rosenfeld, 2015; Sandman, Glynn, & Davis, 2013). Sandman and colleagues have proposed an early-life viability-later-life vulnerabilty trade-off for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent analyses in the Lifestyle and environmental factors and their Influence on Newborns Allergy risk (LINA) study reported differentially methylated regions in calcium- and Wnt-signaling pathways involved in lung maturation prenatally among children exposed to increased prenatal stress who went on to develop wheeze 54 . Other evidence indicates that stress-induced epigenetic changes that influence development can be sex specific 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…At the interface of maternal experience and the developing fetus lies the placenta, a tissue that serves as a gatekeeper of maternal signals, admitting critical nutrients and gasses from maternal circulation while blocking pathogenic intruders including viruses and bacteria (51). Here we focus our discussion on the evidence for epigenetic mechanisms in the placenta to promote sex-specific offspring responses to prenatal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus our discussion on the evidence for epigenetic mechanisms in the placenta to promote sex-specific offspring responses to prenatal stress. For additional discussion on the involvement of the placenta in transmitting maternal signals to the developing fetal brain see reviews (51–54). …”
Section: Introductionmentioning
confidence: 99%